Two additional species of Labiobaetis Novikova and Kluge, 1987 (Ephemeroptera, Baetidae) from Tamil Nadu, India - Srinivasan, Pandiarajan; Sivaruban, T.; Sruthi, S. P.; Barathy, S.; Isack, Rajasekaran; Nadar, M. S. A. Muthukumar (Aquatic insects, 2025)
Based on larvae collected from the Western Ghats in South India, a new species of Labiobaetis Novikova and Kluge, 1987 is described. Labiobaetis gattolliati sp. n. belongs to the L. sumigarensis group of species and is compared to other members of the group as well as to other Labiobaetis species from India. Labiobaetis freitagi Kaltenbach, Garces, and Gattolliat, 2020 is recorded for the first time from India. With this discovery, the species number of the L. sumigarensis group in India has increased to four. http://www.zoobank.org/urn:lsid:zoobank.org:pub:99937EEC-19E8-415B-9848-C243D9C91466